Pigs and profits: hybrids of animals, technology and humans in Danish industrialised farming. (November 2013) - Anneberg, Inger; Vaarst, Mette; Bubandt, Nils
<x xml:space="preserve">Abstract</x> Farm animals live and die as part of a food production system rich in paradoxes. One central paradox of modern farming revolves around the classic anthropological opposition between 'nature' and 'culture'. Inspired by Bruno Latour's diagnosis of the processes of purification and mediation that attend the separation between 'nature' and 'culture' in the modern constitution, we trace how this paradox plays itself out on Danish pig farms. The paper argues that, although they have to be consistently ignored, hybrids of various kinds are essential to the co‐production of meat and profit on industrial, debt‐ridden and highly effective farms in the Western world.